(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The southeastern border of the Laguna Merín Basin (Rocha Department, East Uruguay) consists of Mesozoic volcanic deposits of the Puerto Gómez and Arequita formations, overlain by a sedimentary cover of Cenozoic and recent deposits. Wellpreserved lava flow and pyroclastic deposits have been identified in the Arequita Formation after detailed mapping (1.50.000) in Sierra de los Ajos region. The present study focuses on the petrographic characterization of this felsic volcanism, with special emphasis on the pyroclastic units. Differences in the structural and petrographic distribution of these volcanic units are related to the N20ºE trending India Muerta Lineament. East of this lineament, SiO2-rich rhyolites and pyroclastic deposits (ignimbrites) are present whereas to the west, the volcanic rocks are mainly represented by basic to felsic lavas. Based on petrographic features and regional distribution, explosive mechanisms have been assigned to some of the volcanic units, interpreted as pyroclastic flow and pyroclastic surge deposits.